(untitled) (Praxis Educativa, 2024)
Before the social mobilizations of October/2019 broke out, the Chilean secondary education curriculum was modified. The reform implied transformations in the subject of History. The literature argues that curricular changes impact pedagogical practices, teachers and teacher identities. This research explores the identity positioning assumed by four history teachers in the face of the curricular transformations of their subject. The results of the qualitative research show the teaching identity declared during the initial application of the curricular reform; it outlines a positioning discourse that rejects the ideological assumptions of the curricular change and reveals an identity positioning that (re)locates the most relevant dimensions of the teaching identity constructed by the teachers. In passing, it evidences the critical position in the face of a curricular reform that imposes a new order to the professional status of teachers, expressed in the weakening of the exercise of the autonomy of history teachers.